Proses Pembuatan Item Tes OLIVE, Online Listening For Individual Practice - Yohana Ika Harnita Sari (JLA (Jurnal Lingua Applicata), 2017)
This article aims at describing the test item making process in developing OLIVE, Online Listening for Individual Practice. OLIVE is a combination of CALL (Computer Assisted Language Learning) and ICT (Information Communication Technology), which is an e-learning format. It is a web application prepared by Sekolah Vokasi Universitas Gadjah Mada Yogyakarta to enhance listening skill for non-English major students. OLIVE provides supplementary listening materials in the form of test which can be self-accessed online outside the classroom. There are four parts of the listening practice served in OLIVE; Short Conversation, Question-Response, Longer Conversation, and Talks. Meanwhile, the process of the test making includes design, operationalization, and administration.